2007
DOI: 10.1200/jco.2007.11.7093
|View full text |Cite
|
Sign up to set email alerts
|

Moderators of Interventions Designed to Enhance Physical and Psychological Functioning Among Younger Women With Early-Stage Breast Cancer

Abstract: A B S T R A C T PurposeTo identify factors that condition or moderate the impact of a previously described set of interventions on psychological and physical adjustment after diagnosis and treatment for earlystage breast cancer. Patients and MethodsYounger women (age Ͻ 51 years, N ϭ 252) with early-stage breast cancer within 2 months of having completed active nonhormonal adjuvant therapy were randomly assigned to a three-arm clinical trial, consisting of a control arm, an education arm, and a nutrition arm. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
50
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 37 publications
(10 reference statements)
3
50
0
1
Order By: Relevance
“…However, while personality traits were significantly associated with social support, they only accounted for a proportion of the variance in perceived social support. Intervention strategies should focus on the more dynamic changeable personality characteristics, like poor coping skills and poor psychosocial resources, instead of the more static dispositional traits [57].…”
Section: Discussionmentioning
confidence: 99%
“…However, while personality traits were significantly associated with social support, they only accounted for a proportion of the variance in perceived social support. Intervention strategies should focus on the more dynamic changeable personality characteristics, like poor coping skills and poor psychosocial resources, instead of the more static dispositional traits [57].…”
Section: Discussionmentioning
confidence: 99%
“…the effects of a food intervention and micronutrient supplements with levels that are realistically achievable by food alone on self-reported infection, nutritional status and immune function in community-a clinical trial to determine if an educational intervention and a nutritional intervention could enhance physical and psychological functioning among younger women completing treatment for early-stage breast cancer Scheier et al(12) Examineswhether the main intervention effects reported in Scheier 2005 were moderated or conditioned by other factors Wardle 2000 176 Adults with raised serum cholesterol levels Depression score (BDI) Lipids levels, mood, cognitive function Designed to evaluate the effects of cholesterol-lowering dietary treatments on mood and cognitive functioning in adults with raised serum cholesterol levels Imayama 2011 439 Postmenopausal women 50-75 years of age; BMI ≥ 25·0 kg/m 2 (if AsianAmerican, BMI ≥ 23·0 kg/the individual and combined effects of dietary weight loss and/or exercise interventions on HRQOL and psychosocial factors (depression, anxiety, stress, social support) Jenkinson 2009 389 Men and women aged 45 years and over with knee pain and BMI ≥ 28·0 kg/m 2 Reduction in pain score WOMAC stiffness subscale, WOMAC physical function subscale, hospital and anxiety depression rating scale, bodily pain and physical function domains of the SF-36To determine whether individualised interventions of diet and quadriceps-strengthening exercise reduce knee pain in community-derived overweight and obese adults aged 45 years and over. To examine the effects of these interventions on knee stiffness, physical function and participants in a diet-plus-exercise weight-loss programme improved on psychological outcomes more than participants in a diet-only weight-loss programme or participants in an assessment-only control groupNieman 2000 91 Obese females; 25-70 years of age; in good health with no known diseases; BMI of 25·0-50·0 kg/m 2 ; not experiencing 'salient emotional or mood problems' Psychological general wellbeing and mood state (e.g.…”
mentioning
confidence: 99%
“…No. Research on unmitigated communion reveals that women tend to score higher on unmitigated communion than men (Helgeson & Fritz, 2000;Helgeson et al, 2007;Scheier et al, 2007) and that these scores have predictive power in perceived HIV risk and involvement in prevention activities (Helgeson & Fritz, 2000). We assumed that African American women scoring higher on the UCS would have poorer relationships with men and hence have lower perceived effectiveness in discussing condom use.…”
Section: Discussionmentioning
confidence: 98%
“…The literature shows that people high in unmitigated communion had difficulty fostering healthy relationships (Helgeson & Fritz, 2000;Helgeson et al, 2007;Scheier et al, 2007). People high in UCS found it difficult to honestly communicate with others due to their fear of losing these relationships.…”
Section: Women's Perceived Power In Relationships and Reports Of Phymentioning
confidence: 97%
See 1 more Smart Citation